Does a firm's exposure to ethical issues matter to financial markets? A governance perspective - Groupe de Recherche en Droit, Economie et Gestion, Valbonne; Cormier, Denis; Magnan, Michel (Valbonne, 2014)
"This paper investigates if a firm's ethical issues, in conjunction with its governance, affect its standing within financial markets. A firm's ethical reputation arises from its involvement in ethical violations and incidents while a comprehensive index proxies for governance. We assess a firm's standing within financial markets through two complementary perspectives, i.e., the level of information asymmetry between managers and investors as inferred from analyst forecast dispersion and analyst forecast error and the relation between a firm's earnings and its stock market valuation (value relevance). Our results suggest that a firm's ethical reputation affects financial analysts' forecasts as well as the stock market value assigned to its reported earnings. Moreover, it appears that corporate governance moderates such relations, with strong (weak) governance compensating for a weak (strong) ethical reputation. Overall, our evidence shows that ethical issues do not seem to pay."